2014
DOI: 10.1016/j.urology.2014.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Can Selective Arterial Clamping With Fluorescence Imaging Preserve Kidney Function During Robotic Partial Nephrectomy?

Abstract: Objectives To compare renal functional outcomes in robotic partial nephrectomy (RPN) with selective arterial clamping guided by near infrared fluorescence (NIRF) imaging to a matched cohort of patients who underwent RPN without selective arterial clamping and NIRF imaging. Methods From April 2011 to December 2012, NIRF imaging-enhanced RPN with selective clamping was utilized in 42 cases. Functional outcomes of successful cases were compared with a cohort of patients, matched by tumor size, preoperative eGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 31 publications
(38 reference statements)
3
55
1
1
Order By: Relevance
“…Compared to standard arterial clamping, early results showing significantly superior post-operative kidney function at discharge, and a trend towards significance at 3 months [8].…”
Section: Firefly© Imaging Systemmentioning
confidence: 93%
See 3 more Smart Citations
“…Compared to standard arterial clamping, early results showing significantly superior post-operative kidney function at discharge, and a trend towards significance at 3 months [8].…”
Section: Firefly© Imaging Systemmentioning
confidence: 93%
“…A fluorescent contrast agent is administered intravenously, which emits light in the near-infrared wavelength (700-850 nm) after activation by a light emitting diode [8]. The light, not visible to the human eye, is recorded using a charge-coupled device camera.…”
Section: Fluorescence Image-guided Robotic Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study assessing the intraoperative use of NIR with indocyanine green reported benefit, in terms of short-term renal function, when NIR imaging was utilised to enable selective renal arterial clamping, although this benefit was attenuated at later follow-up [45]. However, a separate study from the same group found that NIR with indocyanine green was unreliable in identifying malignancy, as correlated with final histology [46].…”
Section: Near Infrared Imaging With Fluorophoresmentioning
confidence: 99%